Diagnostic accuracy of DPP Fever Panel II Asia tests for tropical fever diagnosis. - Sandhya Dhawan; Sabine Dittrich; Sonia Arafah; Stefano Ongarello; Aurelian Mace; Siribun Panapruksachat; Latsaniphone Boutthasavong; Aphaphone Adsamouth; Soulignasak Thongpaseuth; Viengmon Davong; Manivanh Vongsouvath; Elizabeth A Ashley; et al. (Public Library of Science (PLoS), 2024)
Background Fever is the most frequent symptom in patients seeking care in South and Southeast Asia. The introduction of rapid diagnostic tests (RDTs) for malaria continues to drive patient management and care. Malaria-negative cases are commonly treated with antibiotics without confirmation of bacteraemia. Conventional laboratory tests for differential diagnosis require skilled staff and appropriate access to healthcare facilities. In addition, introducing single-disease RDTs instead of conventional laboratory tests remains costly. To overcome some of the delivery challenges of multiple separate tests, a multiplexed RDT with the capacity to diagnose a diverse range of tropical fevers would be a cost-effective solution. In this study, a multiplex lateral flow immunoassay (DPP Fever Panel II Assay) that can detect serum immunoglobulin M (IgM) and specific microbial antigens of common fever agents in Asia (Orientia tsutsugamushi, Rickettsia typhi, Leptospira spp., Burkholderia pseudomallei, Dengue virus, Chikungunya virus, and Zika virus), was evaluated. Methodology/principal findings Whole blood (WB) and serum samples from 300 patients with undefined febrile illness (UFI) recruited in Vientiane, Laos PDR were tested using the DPP Fever Panel II, which consists of an Antibody panel and Antigen panel. To compare reader performance, results were recorded using two DPP readers, DPP Micro Reader (Micro Reader 1) and DPP Micro Reader Next Generation (Micro Reader 2). WB and serum samples were run on the same fever panel and read on both micro readers in order to compare results. ROC analysis and equal variance analysis were performed to inform the diagnostic validity of the test compared against the respective reference standards of each fever agent (S1 Table). Overall better AUC values were observed in whole blood results. No significant difference in AUC performance was observed when comparing whole blood and serum sample testing, except for when testing for R. typhi IgM (p = 0.04), Leptospira IgM (p = 0.02), and Dengue IgG (p = 0.03). Linear regression depicted R2 values had ~70% agreement across WB and serum samples, except when testing for leptospirosis and Zika, where the R2 values were 0.37 and 0.47, respectively. No significant difference was observed between the performance of Micro Reader 1 and Micro Reader 2, except when testing for the following pathogens: Zika IgM, Zika IgG, and B pseudomallei CPS Ag. Conclusions/significance These results demonstrate that the diagnostic accuracy of the DPP Fever Panel II is comparable to that of commonly used RDTs. The optimal cut-off would depend on the use of the test and the desired sensitivity and specificity. Further studies are required to authenticate the use of these cut-offs in other endemic regions. This multiplex RDT offers diagnostic benefits in areas with limited access to healthcare and has the potential to improve field testing capacities. This could improve tropical fever management and reduce the public health burden in endemic low-resource areas.